An Analysis of Islamic Criminal Justice Regarding the Validity of Audio Recordings as Evidence - Risna Dayanti; Zulkarnain (Al-Risalah, 2025)
This study examines the validity of audio recordings as evidence in both Indonesian criminal law and Islamic criminal law, in response to technological advancements in legal proof mechanisms. The objective is to explore how audio recordings are recognized and positioned within these two legal systems. The research employs a normative juridical approach through a literature review. The findings indicate that audio recordings are legally recognized as electronic evidence in positive law under Law No. 1 of 2024 concerning Electronic Information and Transactions, although they are not explicitly regulated in the Indonesian Criminal Procedure Code (KUHAP). In Islamic criminal law, audio recordings can be accepted as qarinah (strong indication) or bayyinah (clear evidence), particularly in taʿzir cases, provided they meet authenticity requirements and do not contradict the principles of sharia justice. This study underscores the importance of integrating positive law with Islamic legal values to address the challenges of legal evidence in the digital era.